Augmented Reality (AR) Tools for Vocabulary Acquisition - Ibrohimova Muxtasarxon Masumxon qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This paper explores the use of Augmented Reality (AR) as an innovative tool for enhancing vocabulary acquisition in language learning environments. AR blends digital elements with the real world, offering learners immersive and interactive experiences that can strengthen word retention, comprehension, and contextual usage. By overlaying images, sounds, and animations onto physical objects, AR helps make abstract vocabulary concepts more concrete and memorable. The study examines the pedagogical benefits of AR, such as increased learner engagement, multimodal input, and contextualized learning. It also addresses challenges related to accessibility, technological infrastructure, and teacher training. Findings suggest that AR can be a powerful supplement to traditional vocabulary instruction when implemented thoughtfully and with clear learning objectives.